Analysis of Fourth-Grade Students’ Literacy Skills in Identifying Intrinsic Elements and Moral Values in Legend Stories at SDN 2 Selebung Ketangga - Nila Niswatin; Jumatriadi; Umar Bakri (Indonesian Journal of Education and Science, 2026)
This study was motivated by the need to understand how primary school students construct meaning from legend stories, particularly in identifying intrinsic elements and moral values. The study aimed to analyze fourth-grade students’ literacy skills in identifying intrinsic elements and moral values in legend stories and to examine factors influencing their performance. The study employed an explanatory sequential mixed-methods design involving 20 fourth-grade students at SDN 2 Selebung Ketangga, Indonesia. Quantitative data were collected through a literacy test based on the legend Keong Mas and analyzed using descriptive statistics, while qualitative data were obtained through classroom observations, semi-structured interviews, and documentation and analyzed through thematic and interactive analysis. The findings showed that students’ literacy skills in identifying intrinsic elements were generally good, with a mean score of 81.25; 75% of students achieved good to very good performance. Characters and characterization (95%) and setting (90%) were the strongest aspects, whereas plot (70%) and theme (75%) were more challenging. Students’ ability to identify moral values was also good, with a mean score of 79.50; however, only 65% could provide logically supported explanations. Reading fluency, reading interest, motivation, parental support, school literacy programs, and teacher guidance influenced performance. The study concludes that legend stories can integrate literacy, literary analysis, and moral learning, although instruction should emphasize deeper interpretation and evidence-based reasoning.